RISE: Green research event @ Borneo Jazz Festival / Dr Norol Hamiza Zamzuri, Nor Azzura Nordin and Zakiyah Hasan - Zamzuri, Norol Hamiza; Nordin, Nor Azzura; Hasan, Zakiyah (Office of the Deputy Vice-Chancellor (Research & Innovation), 2021)
The lack of knowledge among event organisers about running a green event has resulted in a demand for an interdisciplinary area of knowledge within the Faculty of Business and Management and the Faculty of Art and Design.